Giant Congenital Melanocytic Nevi and Neurocutaneous Melanosis - Catarina Araújo; Cristina Resende; Francisco Pardal; Celeste Brito (Case Reports in Medicine)
Introduction. The major medical concern with giant congenital melanocytic nevi CMN is high risk of developing cutaneous melanoma, leptomeningeal melanoma, and neurocutaneous melanocytosis. Case Report. A 30-year-old woman with a giant congenital melanocytic nevus covering nearly the entire right thoracodorsal region and multiple disseminated melanocytic nevi presented with neurological symptoms. Cerebral magnetic resonance imaging revealed a large expansive lesion in the left frontal region. Postsurgically pathological diagnosis revealed characteristics of melanoma. Immunohistochemical examination showed S100(+), HMB45(+), MelanA(+), and MiTF(+). She received radiotherapy with temozolomide followed by two more chemotherapy cycles with temozolomide. She followed a rapidly progressive course, reflecting widespread leptomeningeal infiltration, and she died of multiorgan failure seven months after diagnosis of cerebral melanoma. Discussion. This patient was diagnosed as having a neurocutaneous melanosis with malignant widespread leptomeningeal infiltration. Diffuse spinal involvement is unusual and is described in only another patient.